Implementasi Akuntansi Dan Perpajakan Untuk Generasi Milenial Dalam Menghadapi Era 5.0 - Ferry Irawan; Andri Marfiana; Agus Sunarya (PT WIM Solusi Prima, 2022)
Millennials have different characteristics from other generations. This generation interacts earlier with devices and information & communication technology at a very young age. On the other hand, the millennial generation is also known as a generation that tends to be more pragmatic in life. The current millennial generation, especially those in high school is the generation that will be the next leaders in the next 20 years. The development of technology that is very dynamic and fast at this time really changes many things, including employment opportunities for the younger generation. The seminar entitled “accounting and taxation for the millennial generation in facing Era 5.0” aims to provide knowledge and awareness about the importance of accounting and taxation in the future. This seminar was carried out with two approaches: face-to-face, and also relay through the youtube channel. The seminar participants consisted of teachers and students of SMK accounting programs in Tangerang City. There were 60 participants who attended directly, while around 100 participants who followed through the YouTube channel. The seminar activity is divided into three lecture sessions, and a question and answer session. Generasi milenial memiliki karakteristik yang berbeda dengan generasi lainnya. Generasi ini lebih cepat berinteraksi dengan gawai dan teknologi informasi & komunikasi di usia yang sangat muda. Di sisi lain, generasi milenial juga dikenal sebagai generasi yang cenderung lebih pragmatis dalam menjalani kehidupan. Generasi milenial saat ini khususnya yang duduk di bangku SLTA (sekolah lanjutan tingkat atas) merupakan generasi yang akan memimpin Indonesia dalam waktu 20 tahun mendatang. Perkembangan teknologi yang sangat dinamis dan cepat saat ini sungguh mengubah banyak hal, termasuk lapangan pekerjaan bagi generasi muda. Seminar dengan tema akuntansi dan perpajakan untuk generasi milenial dalam menghadapi Era 5.0 bertujuan untuk memberikan pengetahuan dan kesadaran mengenai pentingnya akuntansi dan perpajakan di masa depan. Seminar ini dilaksanakan dengan dua pendekatan yaitu secara tatap muka langsung, dan juga relay melalui kanal youtube. Peserta seminar terdiri dari guru pendamping dan siswa/siswi SMK program akuntansi di Kota Tangerang. Peserta yang hadir secara langsung sebanyak 60 orang, sedangkan peserta yang mengikuti melalui kanal youtube sekira 100 orang. Kegiatan seminar dibagi menjadi tiga sesi materi dan satu sesi tanya jawab.